Multicenter multiplatform pattern-of-practice analysis of single-isocenter multitarget stereotactic radiosurgery - Thomann, Benedikt; Fechter, Tobias; Fischer, Johannes; Runz, Armin; Roers, Julian; Ludwig, Ute Ariane; Grehn, Melanie; Grohmann, Maximilian; Ziemann, Christian; Judge, Michael; Baus, Wolfgang; Grahle, Michelle; et al. (Strahlentherapie und Onkologie, 2025)
Purpose Single-isocenter multitarget stereotactic radiosurgery (SIMT SRS) offers enhanced clinical efficiency for treating multiple brain metastases. However, it introduces additional uncertainties, such as off-center dose and beam profile inaccuracies, as well as quality assurance (QA) challenges, complicating its implementation. This study aims to evaluate different SIMT SRS approaches. Methods We collected and analyzed SIMT SRS protocol and infrastructure parameters from 23 radiotherapy centers across Germany, Austria, and Switzerland, encompassing immobilization systems, computed tomography (CT) protocols, linear accelerators, treatment planning systems, beam configurations, imaging techniques, and QA practices. Consensus, deviations, and compliance with current guidelines were assessed. Subsequent studies will include on-site measurements, evaluation of treatment plan quality and delivery accuracy, and correlation of these findings with the analyzed protocols to identify potential links between protocol parameters and clinical outcomes. Results There is consensus (at least 80% agreement) for a CT slice thickness of ≤1mm, the need for six-degree-of-freedom patient setup correction, and noncoplanar treatment. There is notable variability for intrafraction imaging (used by 70%), minimum accepted planning target volume diameter (ranging from 2-10mm), SRS QA, and general plan parameters, such as photon energy and number of treatment fields. There is also high variability in employed linear accelerator models and treatment planning systems. Conclusion These findings highlight a lack of standardization in SIMT SRS practices. Combined with future measurements correlating protocols to treatment quality, our study will provide a foundation for recommendations to support the safe and standardized implementation of SIMT SRS.
Online veröffentlicht: 10. Juli 2025
Gesehen am 22.09.2025